Assessment of the Economic Value of Mangrove Resources - Hillary, Janne; Ekowati, Titik; Setiawan, Bambang (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Mangrove resource that people often visit, has characteristics that are quite vulnerable to environmental disturbance. Maroon Mangrove Edupark is a mangrove resource in Semarang, located close to Maroon beach and Ahmad Yani International Airport. The presence of mangroves in Maroon Mangrove Edupark, is expected to protect Maroon coastal area and the airport from the coastal disaster, as well as to make it as a new sustainable ecotourism site. This study assessed the benefits of mangrove resource in Maroon Mangrove Edupark according to visitor perception, and provide the economic valuation toward mangrove plantation in there. Economic valuation measurement employed was TCM (Travel Cost Method). The economic surplus value per individual per visit is Rp 173.010,00. The value indicates the benefits of environmental services greater than the cost incurred. Besides that, only 35,54% of mangrove forest has been utilized. For optimalizing the values, increasing the number of mangroves were planted along with maintenance should be done.